Personal Care Products in the Aquatic Environment - Díaz‐Cruz, M. Silvia; Barceló, Damià (The Handbook of Environmental Chemistry,, 2015)
This volume offers an overview of the occurrence and distribution of personal care products in continental and marine waters, presents analytical methods and degradation technologies and discusses their impact on human health. Experts from different disciplines highlight major issues for each family of compounds related to their occurrence in the water column as well as in solid and biota samples, methodological strategies for their analysis, non-conventional degradation technologies, (eco)toxicity data and their human and environmental risk assessment. The book also includes a general introduction to personal care products, covering their properties, use, behaviour and regulatory framework, and a final chapter identifying knowledge gaps and future research trends. It will appeal to experts from various fields of research, including analytical and environmental chemistry, toxicology and environmental engineering.